The shaping of gut immunity in cirrhosis - Muñoz, Leticia; Caparrós, Esther; Albillos, Agustín; Francés, Rubén (Frontiers in Immunology, 2023)
Cirrhosis is the common end-stage of chronic liver diseases of different etiology. The altered bile acids metabolism in the cirrhotic liver and the increase in the blood-brain barrier permeability, along with the progressive dysbiosis of intestinal microbiota, contribute to gut immunity changes, from compromised antimicrobial host defense to pro-inflammatory adaptive responses. In turn, these changes elicit a disruption in the epithelial and gut vascular barriers, promoting the increased access of potential pathogenic microbial antigens to portal circulation, further aggravating liver disease. After summarizing the key aspects of gut immunity during homeostasis, this review is intended to update the contribution of liver and brain metabolites in shaping the intestinal immune status and, in turn, to understand how the loss of homeostasis in the gut-associated lymphoid tissue, as present in cirrhosis, cooperates in the advanced chronic liver disease progression. Finally, several therapeutic approaches targeting the intestinal homeostasis in cirrhosis are discussed.